2016
DOI: 10.15326/jcopdf.3.1.2015.0148
|View full text |Cite
|
Sign up to set email alerts
|

Overall and Cardiovascular Safety of Aclidinium Bromide in Patients With COPD: A Pooled Analysis of Six Phase III, Placebo-Controlled, Randomized Studies

Abstract: Background: Aclidinium bromide, an M 3 -receptor-selective, twice-daily (BID), long-acting muscarinic antagonist, is rapidly hydrolyzed in human plasma, resulting in low systemic exposure and urinary excretion. We evaluated the overall and cardiovascular (CV) safety of aclidinium in patients with moderate to severe chronic obstructive pulmonary disease (COPD) by pooling data from 6 randomized, double-blind, placebo-controlled, parallel-group studies of ≥1 month's duration. Methods: Patients were current/former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(7 reference statements)
2
6
0
1
Order By: Relevance
“…Baseline LCQ values in the total population suggested that the impact of symptoms on quality of life was minimal, possibly because of the number of patients with mild cough. Safety outcomes were consistent with those previously reported (11).…”
supporting
confidence: 89%
“…Baseline LCQ values in the total population suggested that the impact of symptoms on quality of life was minimal, possibly because of the number of patients with mild cough. Safety outcomes were consistent with those previously reported (11).…”
supporting
confidence: 89%
“…These findings extend the results of a pooled analysis (n = 2781) of 6 short-term randomized clinical trials in patients with moderate to severe COPD that found no evidence of increased cardiovascular risk with aclidinium vs placebo and a subanalysis of 1607 patients with cardiovascular risk factors that found no difference in the incidence of cardiovascular or cerebrovascular adverse events. 22 In contrast, 2 large case-control studies showed similar increases in risk for both LAMAs and LABAs within COPD indicates chronic obstructive pulmonary disease; RR, rate ratio. A, Least-squares means from a negative binomial regression model, with treatment group, baseline inhaled corticosteroid use, baseline COPD severity, history of Ն1 exacerbation in the past 12 months, and smoking status as factors; the log of the exposure time adjusted for the time the patients experienced exacerbations was an offset variable.…”
Section: Discussionmentioning
confidence: 98%
“…22 The pooled analysis of six phase III studies also showed that there was no increased cardiovascular or cerebrovascular risk with aclidinium bromide versus placebo in patients with moderate-to-severe COPD. 63…”
Section: Device Handlingmentioning
confidence: 99%